GAYA KOMUNIKASI SELEBGRAM SRI WAHYUNI DALAM PRODUCT ENDORSEMENT DI TAKALAR MELALUI MEDIA SOSIAL INSTAGRAM (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This study discusses the marketing communication style carried out by Sri Wahyuni celebrities when endorsing various local products through social media and Instagram. Online business nowadays, attracts attention, especially among the youth. So that advertising is done online. This study aims to determine the communication style shown by Sri Wahyuni celebrities in promoting products. The results of this study show that the communication style of Sri Wahyuni celebrities in product endorsements on Instagram is: (1) medok (accent), Sri Wahyuni has an accent with a thick Makassar accent. (2) chatty, which is characterized by talkativeness. (3) Detail Oriented, characterized by communication in detail explaining something at length but neatly arranged. (4) effective, which is characterized by communication in a language that is easy to understand by Sri Wahyuni's followers. This research uses a qualitative approach with phenomenological methods. Primary data was obtained from Sri Wahyuni celebgram, @galleryshop owner, @nasiudukhauna.id manager, and followers of Sri Wahyuni celebgram. Data were collected using observation, interview, and documentation methods. Data analysis using Miles and Huberman's interactive methods of data reduction, data presentation, and conclusions.